Adiponectin levels in coronary artery ectasia - Dagli, Necati; Ozturk, Unal; Karaca, Ilgin; Yavuzkir, Mustafa; Koca, Suleyman; Akbulut, Handan; Balin, Mehmet (Springer, 2009)
Etiopathogenesis of coronary artery ectasia (CAE), which is defi ned as abnormal dilatation of a segment of the coronary artery to 1.5 times of an adjacent normal coronary artery segment, is unclear. However, it is speculated that CAE develops in the atherosclerosis process through degeneration of coronary artery media layer. Our objective in this study is to compare levels of adiponectin between cases with CAE and normal coronary anatomy, and to examine whether adiponectin plays a role in CAE etiopathogenesis. The study registered a total of 66 cases, consisting of CAE cases (group 1, n = 36) and cases with normal coronary anatomy (group 2, n = 30). Taking coronary artery diameters of the control group cases as the reference, patients with abnormal segments 1.5 times larger than the adjacent segments were accepted as CAE. Serum adiponectin levels were 4.31 +/- 2.02 A mu g/ml in group 1 and 6.73 +/- 4.0 A mu g/ml in group 2 (P = 0.02). High-sensitivity Creactive protein was 4.8 +/- 3.8 mg/l in group 1 and 3.6 +/- 3.4 mg/l in group 2 (P > 0.05). There was a negative correlation between ectatic coronary artery diameter and plasma adiponectin level (P = 0.03; r = -0.339). It was known that adiponectin levels dropped in atherosclerotic heart disease. In this study we found low plasma adiponectin levels in acquired CAE, attributed to atherosclerosis. Therefore, we think that adiponectin might be playing a role in etiopathogenesis and progression of CAE. This in turn may indicate that hypo-adiponectinemia may be useful in revealing a realized risk in CAE. However, larger, randomized, multicenter studies are required to examine the role of adiponectin in the development of CAE.
Keywords: Adiponectin; Adipocytokine; Atherosclerosis; Coronary artery disease; Coronary artery ectasia